Tellurium Vanadate Glasses: V4+colorimetric Measure and Its Effect on Conductivity - McDonald, Lisa; Siligardi, Cristina; Vacchi, Marco; Zieser, Adam; Affatigato, Mario (Frontiers in Materials, 2020)
This research comes as part of a broader resurgence of study on the electrical conductivity of glasses—and the mechanism for electronic motion in the amorphous network—spurred by interest in using glasses as matrices for solid-state batteries, taking advantage of the glasses’ tailorable conductivity, chemical durability, and mechanical strength. The work presented in this study regards the preparation and characterization of some binary glasses belonging to the TeO2–V2O5 system. In particular, we focused on the glasses’ electrical conductivity at room temperature and at higher temperatures as a function of the V4+ ion content in the glass structure. The amount of V4+ in the glass was determined by a colorimetric method. Moreover, density and thermal properties (Tg, Cp) were measured, and scanning electron microscopy (SEM) and X-ray diffraction (XRD) measurements were performed as well.